KELAYAKAN MODUL EKSTRAKURIKULER CRAFTING BUKET DI SDIT QUANTUM MULIA - Sriyatun; Sumarno; Ida Dwijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The influence of gadgets nowadays reduces children's creativity, makes them feel impatient, less active in collaboration, tends to get stressed easily, and is unable to manage time. The objectives of this research are (1) Describe the level of validity of the craft extracurricular module at SDIT Quantum Mulia, (2) Describe learning outcomes with the craft extracurricular module at SDIT Quantum Mulia, (3) Develop creativity. The research uses a development model, namely there are 5 stages: a) analyzing the product to be developed, b) product development, c) expert validation and revision, d) module readability test, e) final product (bouquet craft module). Criteria for compiling modules must include title, competencies, learning objectives, learning materials, learning procedures, practice questions, as well as evaluation or assessment to measure students' abilities in learning. The research methods are validation rubrics, product results assessment and student response questionnaires. The analysis technique used is quantitative descriptive. Research steps 1. Analysis of module needs 2. Develop initial product: designing and compiling extracurricular bouquet skills modules, 3. Validation Test: Media experts and material experts 4. Readability test of extracurricular modules at SDIT Quantum Mulia 5. Final product bouquet skills. The media expert validation results were 93.75% suitable for use and 6.25% were not suitable for use, while the material expert validation results were 96.67% suitable for use and 3.33% were not suitable for use. In this case, validation of media experts and material experts from 3 teacher respondents. From the validation results of module readability on the understanding of grade 5 students at SDIT Quantum Mulia, there were 76.77% who were very good in assessing, 9.96% were good, 6.78% were quite good and 6.49% were not good.